Quality Evaluation of Entrepreneurship Education in Chinese Medical Colleges–From the Perspective of Student Cognition - Li, Yuhui; Shen, Wei; Lv, Yijun (Frontiers in Psychology, 2020)
The effectiveness evaluation of entrepreneurship education has become a key issue to improve the quality of entrepreneurship education. The quality of entrepreneurship education was empirically analyzed through a questionnaire survey conducted within 70 medical colleges and universities in China and 16660 valid questionnaires were obtained. The datasets were processed with a classic analysis tool, SPSS. Several findings were revealed by the research. The popularity of entrepreneurship course in China’s medical schools was low, with obvious characteristics of fragmentation in curriculum design; the entrepreneurship practice for medical students was far from open and not effectively integrated with the market trend; the current policies in China do not provide additional support for medical entrepreneurship and the lack of funds has been the main obstacle for medical students owned start-ups; the teacher-student collaboration should be an important vessel to improve the quality of entrepreneurship education. It is recognized in this paper that in the future, medical schools in China should build individualized and diversified medical entrepreneurship education curriculum system, strengthen the openness of medical students' entrepreneurship practice, build a multi-channel financial support platform and create a major-innovation integration mechanism.